Shakespeare from a Minority Point of View: Ted Lange’s Othello - Seunghyun Hwang (American Studies in Scandinavia, 2017)
Othello (1989) is a little-known independent film directed and produced by Ted Lange. Released at the end of the 1980s, a decade of mounting racial tension in the United States, the film offers an interpretation of Shakespeare from a minority point of view. This examination of the director’s motives and directorial choices reveals the strategies employed by Lange to make Shakespeare relevant and more available to a non-traditional audience, especially to African-Americans. In addition, delving into the acceptance and distribution difficulties that Ted Lange faced gives insight into the issue of discriminatory assumptions related to applying a minority point of view to a traditionally highbrow domain.